2007
DOI: 10.1016/j.jpsychores.2007.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among patients with a brain tumor and their carers

Abstract: The degree of detriment to quality of life by a brain tumor for patients and that for their carers are similar and clinically significant. The association between the FACT-G subscales and the HADS indicates that improvements could be achieved by alleviating emotional distress and improving functional well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
111
4
12

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(147 citation statements)
references
References 42 publications
20
111
4
12
Order By: Relevance
“…Without good health and social care, support carers may be tied to the home, leading to difficulties in going to work and accessing support outside of the home. In a study by Janda et al (2007) a correlation was found between carers' and patients' overall quality of life, with patients and carers in the same household reporting similar reductions in emotional and social wellbeing.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Without good health and social care, support carers may be tied to the home, leading to difficulties in going to work and accessing support outside of the home. In a study by Janda et al (2007) a correlation was found between carers' and patients' overall quality of life, with patients and carers in the same household reporting similar reductions in emotional and social wellbeing.…”
mentioning
confidence: 98%
“…Poor cognitive functioning has been linked to high levels of stress and anxiety in carers (Pinquart et al, 2003). Managing relationships, cognitive diffi culties, personality changes and symptoms such as fatigue can be exhausting and anxiety provoking for carers (Janda et al, 2007(Janda et al, , 2008. Despite the demands on carers it is reported that for some people, family relationships can become stronger and closer, despite behavioural and personality changes (Cook 2005;Arber et al 2007).…”
mentioning
confidence: 99%
“…On the 200-point FACT-Br scale, the mean patient score was 131.8+27.6 points (median, 135.5; mean FACT-G, 79.2+16.1), which is highly consistent with scores reported in previous studies of QOL in glioma. 3,24 Although our analysis suggested that patients in this study reported total FACT-Br scores that were on average 4.75 (95% CI,1.44 -8.05) points higher than their caregivers reported in simultaneous assessments (P ¼ .008), this difference would not be deemed clinically significant using a benchmark of half of the standard deviation in FACT-Br scores or 13.8 points. 21 Likewise, none of the patient-caregiver differences in subscale scores exceeded the corresponding clinically significant difference thresholds as presented in Table 2.…”
Section: Discussionmentioning
confidence: 57%
“…Irrespective of the level of functioning or disability, the consequences of glioma can hinder patients in participating fully in vocational and social activities, affecting the quality of life (QOL) of both patients and their family members to a great extent (Janda et al 2007;Taphoorn et al 2010;Aaronson et al 2011). As the disease progresses, patients rely more heavily on their loved ones for physical and emotional support.…”
Section: Background Gliomasmentioning
confidence: 99%
“…Especially the quality of life of those caregivers of patients with more aggressive, high-grade tumours appears to be vulnerable compared with both the normative population (Flores et al 2014;Janda et al 2007) and other caregiver populations (Boele et al 2013a). While this negative effect may be attenuated by personality traits and coping strategies (Baumstarck et al 2016), the physical and emotional consequences of caregiving are often hypothesized to influence the quality of care delivered to glioma patients in the home.…”
Section: Consequences Of Family Caregivingmentioning
confidence: 99%